Improving Mechanisms for an Equitable Transition to Low-Carbon Development within the BRICS Framework - A. A. Seregina (Евразийская интеграция: экономика, право, политика)
Nowadays transformational changes are going together with the need to address global environmental and climatic challenges. The BRICS member countries realize the need for a fair energy transition to lowcarbon development both within the association and globally.Aim. The objective of the research is to highlight the priority areas that BRICS member countries need to focus on to ensure an equitable and cost-effective transition to low-carbon development at the global level.Tasks. In order to achieve the objective of the study, it is necessary to analyze the components of the BRICS equitable low-carbon development agenda as well as its applicability at the global level.Methods. The research was conducted using the method of systematic analysis of a wide range of academic and empirical sources. The author adheres to a systematic scientific approach.Results. Through the analysis of key initiatives of the BRICS member countries, including legislative ones, five priority areas on which the BRICS needs to focus on to ensure a fair energy transition at the global scale are identified: removing discriminatory measures in multilateral trade, achieving food security and economic growth, facilitating non-discriminatory access to technology, promoting environment and climate cooperation, and enhancing the human resource potential of the energy sector.Conclusions. The author concludes by noting that such a BRICS sustainable development agenda is capable of initiating energy transition processes on a global scale.